Enhancing educational through blended teaching: an analysis of teaching and learning quality with learning environment and social impacts - Xinfa, Tang; Xuejiao, Yang; Guozu, Hao; Yifei, Sun; Youwei, Wan (Frontiers in Education, 2025)
This paper delves into the challenges and opportunities associated with blended teaching, while analyzing its impact on teaching and learning quality through quantitative methods. It highlights that Blended teaching, fueled by modern educational technologies, holds the potential to significantly enhance teaching standards and student engagement. However, the hybrid model is still in its nascent stages in many contexts, confronting issues such as teaching quality, student adaptation, management mechanisms. The paper provides suggestions for reform, including strengthening teacher training, modifying learning behaviors, expanding supervision, and incorporating sustainable practices. Through practical research, it concludes that Blended teaching can improve student satisfaction, academic performance, and promote the sustainable development of education, emphasizing the need for continuous innovation and improvement in educational practices to fully harness its potential.